A new species of Philautus (Anura: Rhacophoridae) from the Eastern Ghats, south-eastern India - Das, I.; Chanda, S.K. (Wildlife Heritage Trust of Sri Lanka, 1998)
A new species of Philautus is described from the vicinity of Vishakhapatnam, Andhra Pradesh in south-eastern India. The new species is compared with congeners from peninsular India and Sri Lanka. Since the members of the genus are restricted to wet evergreen forests of the region, remnant patches of wet forests within a now largely degraded and arid Eastern Ghats are apparently refugia, supporting species that are tolerant of mesic conditions.